Rational choice of tactics in patients with uterine fibroids - T Yu Pestrikova; E A Yurasova; I V Yurasov; A V Chirkov (IP Berlin A.V., 2017)
In the presented review of the literature questions of epidemiology, pathomorphology, pathogenesis, clinic, diagnostics of uterine myomas are considered. Presented are data accentuating the use of the progesterone receptor antagonist drug mifepristone. The therapy of myoma of the uterus by mifepristone is not inferior in effectiveness or safety to analogs of gonadotropin-releasing hormone agonists, and does not have a negative effect on estrogen-dependent extragenital systems and organs (cardiovascular system, bone tissue, mammary glands, etc.), since the serum Estradiol remains at a level corresponding to the early follicular phase of the menstrual cycle.